Analysis of Regency and City Pneumonia Clusters in West Java 2020 - Yusma Yanti; Septian Rahardiantoro (Ilmu Komputer, FMIPA, Universitas Pakuan, 2023)
Pneumonia is an infection of the respiratory tract caused by bacteria, viruses, or fungi. The number of pneumonia cases in West Java is relatively high, therefore, it is necessary to identify some group of regencies/cities in which have a common characteristic, to make it easier to handle. The data used is data on the number of pneumonia cases in 27 regencies/cities in West Java in 2020. In this study, chi-squared test was applied to determine the characteristics of pneumonia spread in West Java. Then, a regression-based analysis by using the Irregular Graph Fused LASSO method was used to provide the cluster of regencies/cities, by considering the adjacent locations of regencies/cities as a penalty matrix. The results obtained that the cases spread unevenly. The number of cases for every 1000 people in each regency/city was relatively high in the eastern part of West Java. There were 6 clusters obtained from 27 regencies/cities, with Pangandaran regency as the location with the highest cases occurred. Depok City and Bekasi City were locations with the lowest number of cases even though they have relatively high population numbers.